Education and working life: VET adults' problem-solving skills in technology-rich environments. (October 2015) - Hämäläinen, Raija; De Wever, Bram; Malin, Antero; Cincinnato, Sebastiano
Abstract: The rapidly-advancing technological landscape in the European workplace is challenging adults' problem-solving skills. Workers with vocational education and training need flexible abilities to solve problems in technology-rich work settings. This study builds on Finnish PIAAC data to understand adults' (N = 4503) skills for solving problems in technology-rich environments. The results indicate the critical issue that more than two thirds of adults with vocational education and training have weak skills or lack the skills in solving problems in technology-rich environments and that more than one fifth of these adults are at risk. Furthermore, this study indicates that the likelihood of having fragile problem-solving skills is six times higher for adults with vocational education and training than for adults with at least upper secondary qualification. Since the need for problem-solving in technology-rich environments is likely to increase in the future, this study also identifies the indicators for problem-solving skills differences. The models predicting problem-solving skills on the basis of theoretical assumptions as well as empirical support are presented. Our results indicate that adults' lower performance does not seem to be associated with the vocational education and training educational system itself, but is mostly due to age, education in years, occupation, and gender, as well as work-related and everyday life factors. In practice, the models help to develop new approaches to enable novel problem-solving skills in technology-rich environments based on the current European workplace needs. Highlights: The study identifies adults' (N = 4503) problem-solving skills in TRE in Finland. More than two thirds of VET adults have weak skills or lack the skills. This study detects the indicators for skills differences based on the PIAAC data. The models explaining variation in adults' problem-solving skills are presented. The models help to develop new approaches to support problem-solving in TRE.